Altered Long- and Short-Range Functional Connectivity Density in Patients With Thyroid-Associated Ophthalmopathy: A Resting-State fMRI Study - Jiang, Wen-Hao; Chen, Huan-Huan; Chen, Wen; Wu, Qian; Chen, Lu; Zhou, Jiang; Xu, Xiao-Quan; Hu, Hao; Wu, Fei-Yun (Frontiers in Neurology, 2022)
Background and purpose: Although previous neuroimaging studies have demonstrated emotion- and psychology-associated brain abnormalities in patients with thyroid-associated ophthalmopathy (TAO), the changes of brain functional connectivity in TAO were seldom focused. We aimed to investigate interregional and intraregional functional interactions in TAO patients by using resting-state functional MRI (rs-fMRI) with long- and short-range functional connectivity density (FCD) analysis. Methods: Thirty TAO patients and 30 well-matched healthy controls (HCs) were recruited in our study. Long- and short-range FCD values were calculated and compared between two groups. Correlations between long- and short-range FCD values and clinical indicators were analyzed. Results: Compared with HCs, TAO patients showed both increased long- and short-range FCDs in left middle frontal gyrus (MFG), orbital part of superior frontal gyrus (ORBsup) and dorsolateral part of superior frontal gyrus (SFGdor); meanwhile, both decreased long- and short-range FCDs in bilateral postcentral gyrus (PoCG), left superior parietal gyrus (SPG) and inferior parietal (IPL). In addition, TAO patients showed increased short-range FCD in the right SFGdor, bilateral medial part of superior frontal gyrus (SFGmed), left orbital part of middle frontal gyrus (ORBmid) and orbital part of inferior frontal gyrus (ORBinf), as well as decreased short-range FCD in the right supplementary motor area (SMA) and the left paracentral lobule (PCL) than HCs. Moreover, the short-range value in left SFGdor showed a negative correlation with MoCA score (r = -0.501, p = 0.005). Conclusion: Our findings complemented the functional neural mechanism of TAO, and provided potential neuroimaging markers for assessing the psychiatric, visual and emotional disturbances in TAO patients.